PENGARUH CITRA DAN KUALITAS PELAYANAN MELALUI KEPUASAN TERHADAP LOYALITAS PELANGGAN PADA - Renny Widhiastuti; Ari Pradhanawati; Sendhang Nurseto (Universitas Diponegoro, 2014)
Many of the problems faced by the beauty clinic. One of them is customer loyalty. Customer loyalty is influenced by several factors, including the image and quality service. In addition to improving satisfaction also affects customer loyalty. Object of this study is Monalizha Skin Care Semarang. The purpose of this study was to determine the effect of image and quality service on satisfaction and also its influence on customer loyalty in Monalizha Skin Care Semarang. The population in this study is Monalizha Skin Care Semarang customers, totaling 864 people. The study sample 90 respondents, the sampling technique is done using random sampling methods. Methods of data collection using questionnaires. Analysis techniques using simple linear regression analysis and multiple, T test and F test. Variables quality service most impact on satisfaction. The coefficient of determination of quality service to the satisfaction of 49.6%, which means the impact of service quality on satisfaction of 49.6%. Regression analysis showed that the image and service quality has a positive effect on customer satisfaction and loyalty. Conclusion, image and quality service effect on satisfaction and customer loyalty. This proves that the image and good quality service will increase customer satisfaction and ultimately create customer loyalty. The author suggested that Monalizha Skin Care Semarang constantly trying to improve customer satisfaction as a key to increasing customer loyalty by improving the image and quality of service. Things that can be done is to increase the professionalism, innovation of products, maintaining product safety levels, increasing the excellent service and others.